2019
DOI: 10.1021/acscentsci.9b00210
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Information Using Small Organic Molecules

Abstract: Although information is ubiquitous, and its technology arguably among the highest that humankind has produced, its very ubiquity has posed new types of problems. Three that involve storage of information (rather than computation) include its usage of energy, the robustness of stored information over long times, and its ability to resist corruption through tampering. The difficulty in solving these problems using present methods has stimulated interest in the possibilities available through fundamentally differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 27 publications
0
79
0
1
Order By: Relevance
“…Likewise, we believe that the performance of other SAM-based devices can be optimized through molecular dilution without losing the structural order. Recently, Cafferty et al [35] encoded, wrote, stored, and read approximately 400 kb with mixtures of 32 sets of oligopeptides having distinguishable molecular weights in mixed SAMs. Wang et al [34] recently demonstrated that this counter-intuitive approach can be realized in mixed SAMs of Fc-terminated n-undecanethiolate (FcC 11 S; organometallic diode) and n-undecanethiolate (C 11 S) without Fc.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we believe that the performance of other SAM-based devices can be optimized through molecular dilution without losing the structural order. Recently, Cafferty et al [35] encoded, wrote, stored, and read approximately 400 kb with mixtures of 32 sets of oligopeptides having distinguishable molecular weights in mixed SAMs. Wang et al [34] recently demonstrated that this counter-intuitive approach can be realized in mixed SAMs of Fc-terminated n-undecanethiolate (FcC 11 S; organometallic diode) and n-undecanethiolate (C 11 S) without Fc.…”
Section: Discussionmentioning
confidence: 99%
“…The solid-phase synthesis has been a method to synthesize polymers with defined aperiodic sequences [9][10][11][12] . Although sequence-defined polymers with more than 100 repeating units have been synthesized 13,14 , synthesis has largely been limited to sequence-defined oligomers with a limited number of repeating units due to the difficulties associated with the repeated step-bystep addition of individual monomers to achieve high molecular weights [15][16][17][18][19][20][21][22][23][24][25][26] . The iterative convergent method has been widely adopted for the synthesis of dendritic and linear macromolecules with precisely defined chemical structures [27][28][29][30] .…”
mentioning
confidence: 99%
“…Currently, some other molecule storage medium was proposed including oligopeptides 3,13 and metabolomes 4 . It is innovative for these techniques to use amino acids and metabolomes for binary transcoding.…”
Section: Discussionmentioning
confidence: 99%
“…Erlich et. al reported that in their working scheme, the minimum average copy number for data retrieval was around 1.3×10 3 . In this work, we demonstrated that the minimum average copy number for data retrieval is 7×10 3 (Supplementary information), which is consistent with the previous report.…”
Section: High Coding Efficiencymentioning
confidence: 99%